2012
DOI: 10.1111/j.1467-8659.2012.03213.x
|View full text |Cite
|
Sign up to set email alerts
|

Digital Camouflage Images Using Two‐scale Decomposition

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…When asked to choose the better one from the hidden images created by our method and Chu et al's method [CHM*10], our method obtained 69.80% of the total times (95% confidence interval, 63.85% to 75.75%). It also achieved 74.87% against Du et al's method [DJM12] (95% confidence interval, 68.27% to 81.47%). By performing one-sample, one-tailed t tests for the representative state-of-the-art methods, we found that participants preferred our method (p-values 0.001).…”
Section: Verification Of Hidden-image Synthesismentioning
confidence: 83%
See 2 more Smart Citations
“…When asked to choose the better one from the hidden images created by our method and Chu et al's method [CHM*10], our method obtained 69.80% of the total times (95% confidence interval, 63.85% to 75.75%). It also achieved 74.87% against Du et al's method [DJM12] (95% confidence interval, 68.27% to 81.47%). By performing one-sample, one-tailed t tests for the representative state-of-the-art methods, we found that participants preferred our method (p-values 0.001).…”
Section: Verification Of Hidden-image Synthesismentioning
confidence: 83%
“…However, their hidden results include blurring artefacts because of the transformation. Du et al [DJM12] employ the edges of the foreground as clues and formulate the hidden-image synthesis as a blending optimization problem as well. When the contrast of the background is quite low, too many details which are distinct from the surroundings are preserved.…”
Section: Hidden-image Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Tong et al [32] proposed a method to generate hidden images by first detecting edge features of a hidden object, and then finding a suitable embedding place in the background scene using an energy optimizing process. Du et al [33] utilized the contour completion property of human perception to generate digital camouflage images. In the above-mentioned techniques, although the hidden objects were less noticeable than the background, they are still recognizable by any observers.…”
Section: Related Workmentioning
confidence: 99%
“…Tong et al [17] proposed a method to generate hidden images by first detecting edge features of a hidden object, and then finding a suitable embedding place in the background scene using an energy optimizing process. Du et al [18] utilized the contour completion property of human perception to generate digital camouflage images. All the above mentioned techniques aim to hide objects in background images by fooling the human recognition process.…”
Section: Related Workmentioning
confidence: 99%